Basemah Customary Marriage “Kule Berete” on Women’s Inheritance Rights In an Islamic Legal Perspective - Mila Surahmi; Junaidi Junaidi (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
The Besemah community prioritizes the position of boys over girls. Sons are the successors of their father's descendants drawn from one original father, while daughters are prepared to become other people's children who will strengthen their descendants. The eldest son in the Besemah community must remain and reside in his father's house and be responsible for the lives of younger brothers and sisters, especially those who are not yet married so that the Besemah community applies the KULE BERETE marriage system. KULE BERETE marriage is a marriage system that draws a lineage from the father, which results in the wife following her husband. In this marriage system, the husband has absolute rights over wealth, and the first son takes precedence. Besemah custom, in terms of inheritance, still uses customary law to guide the estate distribution between sons and daughters. In the Besemah indigenous community, the population uses the male-majority inheritance system. Majoratinheritance system is one in which the inheritance of parents or ancestral heritage remains intact, not divided among the heirs, but controlled entirely by the eldest son (majorat male). It causes women's loss of position and inheritance rights to receive an inheritance, contrary to Islamic Law.